Motricidad gruesa y su influencia en el desarrollo de la cinética corporal en estudiantes de tercer año de la Escuela de Educación Básica Cesar Ernesto Medina Salinas cantón Baba Provincia Los Ríos - Zambrano Sánchez, Rosa Estefania (2020)
Motricity is a fundamental process for the joint development of the mind in coordination with the muscular and affective, so it was determined that psychomotricity is related to the learning of literacy, this study, which was applied in the students of Third year of the school of Basic Education "Cesar Ernesto Medina Salinas" canton Baba Province Los Ríos, will benefit the authorities, teachers and students. The present degree work seeks to know how gross motor skills and body kinetics affect the expression and movements of students, with the aim of determining the impact that body movements have on the fluidity of third-year students of the Basic Education School “Cesar Ernesto Medina Salinas” This work was carried out based on exploratory, descriptive and bibliographic research, applied to a sample of 35 basic students and 1 teachers of the educational institution, where the results were obtained to arrive at the verification of the hypothesis through a survey made to both entities, giving as a conclusion that teachers do not have a strategy guide for the fluidity of body movements that help students understand what their body movements are, teachers should continue to take courses frequently that enhance and increase the fluency of their students, teaching techniques to process the information which will help to obtain greater ease to the student and for this the teacher must also seize a range of knowledge in such a way that he expresses himself to his students with property.